What Separates Offenders Who are Not Victimized from Offenders Who are Victimized? Results from a Nationally Representative Sample of Males and Females - Alua, Muratova (Victims & offenders, 2024)
There has been considerable interest in understanding victim-offender overlap, including why it occurs and the factors that are responsible for creating it. At the same time, however, there has been a lack of research examining precisely why some offenders are able to escape victimization and yet others are more susceptible to it. The current study sought to address this gap in the literature. To do so, data drawn from the National Longitudinal Study of Adolescent to Adult Health (Add Health) were analyzed. The results revealed that a range of covariates, including low self-control, delinquent peers, social support, parental criminality, intelligence, and poverty, were differentially related to the odds of being victimized among offenders over the life course. We discuss what these findings mean for research on victim-offender overlap and future research in this area.